E-commerce in preferential trade agreements: Implications for African firms and the AfCFTA - Karishma Banga; Mohamed Gharib; Max Mendez-Parra; Jamie Macleod (Overseas Development Institute (ODI), 2021)
At continent level, the African Continental Free Trade Area (AfCFTA) negotiations are scheduled to include a protocol on e-commerce under Phase III, presenting a unique opportunity for African countries to collectively establish common positions on e-commerce, harmonise digital economy regulations and leverage the benefits of e-commerce. In this paper, we examine developments in e-commerce negotiations, their implications for African businesses and the role of the AfCFTA. This is done using desk-based research, complemented with primary survey data from 31 African businesses predominantly across Kenya, Rwanda and Nigeria, and in-depth semi-structured telephone interviews with 15 firms, the majority of which are small enterprises. A core finding is that e-commerce is now more important than ever, with scope for the AfCFTA to provide a guiding framework for data protection, privacy policies and stronger enforcement. The analysis in this paper shows that facilitating a regional dialogue in Africa to open opportunities to cross-border e-commerce trade is key.
Keywords: 330; Africa; Trade & investment; Technology; Tax